Simple One-Step and Rapid Patterning of PDMS Microfluidic Device Wettability for PDMS Shell Production - Feng, Chunying; Takahashi, Kohei; Zhu, Jianan (Frontiers in Bioengineering and Biotechnology, 2022)
Double emulsion droplets with controlled size and internal structure are a promising platform for biological analysis, chemical synthesis, and drug delivery systems. However, to further ‘democratize’ their application, new methods that enable simple and precise spatial patterning of the surface wettability of droplet-generating microfluidic devices are still needed. Here, by leveraging the increase in hydrophilicity of PDMS due to the plasma-treatment used to permanently bond to glass, we developed a one-step method to selectively pattern the wettability of PDMS microfluidic devices for double emulsion generation. Our results show that both Aquapel-treated and PFDTES-treated devices are functional, showing the generality of our method. With the resulting microfluidic devices, both water-in-oil-in-water (w/o/w) and oil-in-water-in-oil (o/w/o) double emulsion droplets can be produced. Using a PDMS mixture containing cross-linking agents, we formed PDMS microcapsules by solidifying the shell layer of water-in-PDMS-in-water double emulsions. We also characterize the morphological properties of the generated droplets/microcapsules. We anticipate the method developed in this work could be used in a broad range of applications of double emulsion droplets.